Gendered hierarchies and world order: A critical analysis of the instrumentalization of gender within the UN discourse on gender vulnerability to AIDS - Jenkins, Sara Anne (University of Ottawa (Canada), 2009)
This thesis is primarily concerned with the concept of gender. It is interested in gender both insofar as it shapes vulnerability, as well as the degree to which particular understandings of gender are instrumental to the functioning of the current world order. This thesis argues that the UN discourse on gender vulnerability to AIDS is an example of the manner in which gender is instrumentalized and made to support a neoliberal globalized model of development and thus of a neoliberal world order. This argument is based upon a discourse analysis of key UN documents on the topic of gender vulnerability to AIDS which is guided by a critical gendered theoretical framework. While it is clear that no established counter-hegemonic or transformative discourse which would appreciably threaten the status quo is present, the existence of spaces for critique points to the potential for the emergence of sites of resistance within the UN.
Keywords: Health Sciences, Public Health.; Political Science, International Law and Relations.; Gender Studies.